Neural basis of linguistic factors involved in thought: an fMRI study with native signers - Hino, Rimi; Umejima, Keita; Wada, Natsumi; Takei, Wataru; Kawasaki, Yoshiko; Sakai, Kuniyoshi L. (Frontiers in Psychology, 2025)
Linguistic factors are critically involved in our conscious thinking processes, but neuroscientific evidence of their involvement is scant. To examine commonalities that underlie reasoning and language tasks, we prepared illustrative quizzes under five conditions in a Reasoning task: Context, Fill-in, Rotation, Sequence, and Analogy. These conditions differentially involved linguistic factors of the recursive, propositional, and clausal, as well as non-linguistic factors. We also used story videos in Japanese Sign Language (JSL) in a Sign task as a language comprehension task. Brain activations measured with functional magnetic resonance imaging (fMRI) were examined for native JSL signers, with the following results. First, in the comparison of the Context condition with the Fill-in condition, which controlled non-linguistic factors, multiple bilateral regions were activated, including language areas such as the left lateral premotor cortex (L. LPMC) and left inferior frontal gyrus (L. IFG). By using conjunction and region of interest analyses, we clarified two distinct systems, which were differentially recruited under the Sequence and Analogy conditions: the recursive system (L. LPMC/dorsal IFG and right LPMC) and the propositional system (L. IFG), respectively. Secondly, during the Sign task, we identified activations in the L. LPMC, L. IFG, and other temporal regions. Moreover, by focusing on the contextual comprehension processes in the Sign task, we found that the L. IFG and bilateral posterior temporal gyri (pTG) were commonly activated between the Sign task and Context condition. Thirdly, in the bilateral pTG, activations were selective only under the Context condition and not under the other four conditions, confirming its role as the clausal system. We thus successfully identified three critical systems for both language and thought processes.